Kinetics and methane generation potential from dog waste through anaerobic digestion - Albuquerque, Milla Gomes; Ferreira Batista, Fábio; dos Santos, Liliana Andréa; Fernandes Lima Cavalcanti, Jorge Vinícius; Thomé Jucá, José Fernando; Marques de Arruda, Valmir Cristiano; de Melo Sales Santos, André Felipe (Revista Geama, 2023)
The high and growing number of dogs present in the urban environment and the consequent generation of dog waste (DW) has as a problem the emergence and spread of zoonotic diseases due to inadequate disposal in effluent treatment systems, sanitary landfills, and urban drainage. Disposal of these wastes is often neglected due to the false perception of low impact when evaluating the quantities generated in a single household. An option for the treatment of these residues is anaerobic digestion (AD) with the consequent production of methane (CH4). This study determined the methane generation potential of DW, also testing the influence of the use of sodium bicarbonate (NaHCO3) as alkalizing AD in residue tests in addition to bicarbonate (DWb). The methane potential resulted in 99.63 NmL.gVS-1 (DWb) and 123.79 NmL.gVS-1 (DW). The insertion of sodium bicarbonate (NaHCO3) did not present an advantage in terms of improvement in the methane generation potential or the concentration of methane in the biogas. Five kinetic models were tested, all of which were compatible with the experimental data obtained. However, the Cone model was the one that presented the best fit for all configurations (DWb and DW) tested.